2018
DOI: 10.1051/e3sconf/20183106010
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Soil Properties and Organophosphate Residues From Agricultural Land in Wanasari Sub-District, Brebes, Indonesia

Abstract: Abstract.Organophosphates have been used to eradicate pests and prevent losses from harvest failures caused by pest attack. It is undeniable that the organophosphate persist in soil. This study aims to identify the organophosphate residue and soil properties include pH, soil texture, and permeability. The soil samples were taken from cropland in 10 villages, Wanasari sub-district, Brebes, Indonesia. Organophosphate residue determined by gas chromatography using Flame Photometric Detector. Soil texture was dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 8 publications
(7 reference statements)
0
8
1
Order By: Relevance
“…chlorpyrifos is often done carelessly and excessively so that chlorpyrifos residues are often detected in sediments or water surfaces [18]. Based on the evaluation, the residual chlorpyrifos from runoff, spraying, and spillage in streams and water bodies in the agro-ecosystem ranges from 0.01 to 0.1 mg.L -1 [19][20][21] and in soils ranging from 0.011-0.063 mg.kg -1 [9]. In addition, chlorpyrifos has also been shown to induce genotoxicity because it inhibits DNA and protein synthesis at the cellular level [6,22,23].…”
Section: Emailmentioning
confidence: 99%
See 1 more Smart Citation
“…chlorpyrifos is often done carelessly and excessively so that chlorpyrifos residues are often detected in sediments or water surfaces [18]. Based on the evaluation, the residual chlorpyrifos from runoff, spraying, and spillage in streams and water bodies in the agro-ecosystem ranges from 0.01 to 0.1 mg.L -1 [19][20][21] and in soils ranging from 0.011-0.063 mg.kg -1 [9]. In addition, chlorpyrifos has also been shown to induce genotoxicity because it inhibits DNA and protein synthesis at the cellular level [6,22,23].…”
Section: Emailmentioning
confidence: 99%
“…This phenomenon is known to have triggered chemical contamination in the agricultural environment and has been cited as one of the factors causing the decline in local and global amphibian populations [3][4][5][6]. Currently, organophosphate (OPs) pesticides are the most widely used pesticides in agriculture [7][8][9], while these pesticides have relatively no target specifications and are toxic to most non-target organisms, especially amphibians [10,11].…”
mentioning
confidence: 99%
“…Among the synthetic pesticides, oxon-type OPs, such as trichlorfon (TCF) and chlorpyrifos (CPF), are frequently used [4,5]. Despite claims that these OPs do not persist in the environment, some studies have shown that OP residues can, in fact, persist for longer periods in organic soil and reach the drainage systems of croplands [6][7][8]. In Colombia, OPs can be transported to remote areas by leaching or runoff, and these toxins have been detected near and in water sources associated with crops [9], thus affecting non-target organisms [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers worldwide have monitored the levels of pesticide residues in soil and surface water [22][23][24][25][26][27] with varying levels of pesticide residues reported. Likewise, significant quantities of pesticide residues have been reported in cereals, vegetables and fruits [28,29].…”
Section: Introductionmentioning
confidence: 99%